Clinico-pathological and radiological correlation of sino-nasal masses in a tertiary care center - Sahni, Dimple; Kaur, Gagandeep; Verma, Peeyush; Kaur, Rajwant; Singh, Harpal (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Background: The nasal masses are most commonly encountered condition in outpatient department of otorhinolaryngology. The purpose of this study was to show the clinical, radiological and histopathological correlation of sino nasal masses. Methods: This study was conducted on 100 cases with sino nasal masses over a period of 2 years. A provisional diagnosis was made after clinical and radiological investigation which was confirmed with histopathological examination and the findings were correlated. Results: The number of non-neoplastic lesions were more than neoplastic lesions (75% vs 25%). Incidence was highest in the age group of 31-40 year (21%) with male to female ratio of 1.5:1. In our study among non-neoplastic lesion, inflammatory lesion had highest frequency (75%). We found clinical and histopathological correlation in 94.6% cases (p value 0.04). 93.33% cases correlated radiologically and histopathologically (p value 0.04). Conclusions: We concluded that for proper evaluation of sino nasal masses, clinical, radiological, histopathological evaluation should be carried out conjointly. Histopathologic evaluation remains the gold standard.